Strengthening Religious Moderation Through a Digital DaÔÇÖwah Approach Among Payakumbuh Pioneer Youth - Dodi Nofri Yoliadi; Yanti Mulia Roza; Risfi Windya Sari; Thierno Amadou Diallo (Alfuad: Jurnal Sosial Keagamaan, 2025)
This research explores how digital daÔÇÖwah can serve as an effective means of fostering religious moderation within Payakumbuh City Pioneer Youth (P2KP). Applying the Asset-Based Community Development (ABCD) model, this project aimed to enhance both the understanding of religious moderation and technical capabilities among youth members. By working with the Interfaith Harmony Forum (FKUB) in Payakumbuh and utilizing social media platforms, participants learned to communicate balanced religious messages that advocate tolerance, inclusivity, and peace. Evaluation results indicate that the program successfully improved participantsÔÇÖ understanding of religious moderation and digital skills. This initiative presents a model for leveraging digital spaces to cultivate inclusivity, empowering youth to play an active role in a harmonious and diverse society.